Strategy of Zakat Collection during the Covid-19 Pandemic at Padang City (Case Study at LAZ Charity Risalah) - Kamrizal Kamrizal; Nenengsih Nenengsih (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
Currently, zakat management was also affected by the Covid-19 pandemic. The reason was that the muzaki have decreased their income, thus affecting Zakat collection they do. This study aims to determine Strategy of Zakat collection during the Covid-19 pandemic at LAZ Risalah Charity. The researcher used qualitative, while the type of research was descriptive. The results showed that there were six strategies carried out by LAZ Risalah Charity in Padang City in order to increase the zakat collection target during the pandemic period, namely the socialization of the zakat collection program, the socialization of the zakat distribution program, cooperation with zakat management units (UPZ), zakat pick-up services, online, zakat services via transfer and increasing the capacity of Human Resources (HR). Apart from this program, LAZ Risalah Charity also plans to provide digital financial service facilities for muzaki who will pay zakat. Keywords: Zakat in Covid-19 Time, Strategy of Zakat, Zakat Collection